Fremdsprachenunterricht im 21. Jahrhundert: Lerner · Methoden · Herausforderungen - Kautenburger, Monika Dorothea; Rentel, Nadine; Reissner, Christina; Klos, Fabienne; Zipser, Katharina; Giessen, Hans; Nickenig, Christoph; May, Jacqueline; Potzel, Anne; Julich-Warpakowski, Nina; WEERNING, Marion; Mushchinina, Maria; et al. (htw saar (Prof Thomas Tinnefeld), 2025)
This volume explores the contemporary landscape of foreign language education in the 21st century, with a particular focus on three central dimensions: learners, methodologies, and pedagogical challenges. The demands placed on today’s language learners are markedly more complex than in previous decades. While learners are increasingly autonomous and self-directed, questions remain as to whether they are fully prepared to meet the high expectations of global communication and linguistic competence.